2018
DOI: 10.1093/geront/gny051
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Hearing Aid Use Among Older Americans With Hearing Loss

Abstract: Many socioeconomic factors hinder individuals' ability to obtain and use HA, but these obstacles appeared to be mitigated in part when insurance plans provided adequate HA coverage, or when their family/friends provided encouragement to use HA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 26 publications
10
45
0
Order By: Relevance
“…In the CLSA, hearing device use was more common in males than females. Some studies have shown an effect of sex on hearing device use (Staehelin et al, 2011), whereas others have not (McKee et al, 2018;Popelka et al, 2015). Multivariable analyses using CLSA data are required to determine if the differences seen in our study may be explained by sex-or gender-related factors such as age distribution, hearing loss severity, self-perceived disability, socio-economic status and/or audiogram configuration.…”
Section: Discussionmentioning
confidence: 80%
“…In the CLSA, hearing device use was more common in males than females. Some studies have shown an effect of sex on hearing device use (Staehelin et al, 2011), whereas others have not (McKee et al, 2018;Popelka et al, 2015). Multivariable analyses using CLSA data are required to determine if the differences seen in our study may be explained by sex-or gender-related factors such as age distribution, hearing loss severity, self-perceived disability, socio-economic status and/or audiogram configuration.…”
Section: Discussionmentioning
confidence: 80%
“…In the CLSA, hearing device use was more common in males than in females. Some studies have shown an effect of sex on hearing device use (Staehelin et al, 2011), whereas others have not (McKee et al, 2018;Popelka et al, 2015). Multivariable analyses using CLSA data are required to determine if the differences seen in our study may be explained by sex-or gender-related factors such as age distribution, hearing loss severity, selfperceived disability, socio-economic status, and/or audiogram configuration.…”
Section: Hearing and Vision Loss In Canadamentioning
confidence: 80%
“…Looking ahead, employing pretotypes (the term for the approach we used in this study) and prototypes, as well as careful iterative user testing throughout the LVA design process would allow further exploration of these challenges. The stigma of using assistive devices in many other areas has been widely reported including hearing loss 49 and wheelchair use 50 as well as visual impairment 51 . Minimising the potential for perceived stigma and self‐consciousness should therefore be a guiding principle for design.…”
Section: Discussionmentioning
confidence: 99%